Science Citizens: Bridging Knowledge and Action for All - Ramlan Ramlan; Belay Sitotaw Goshu (BIRCU, 2025)
Science education in Ethiopia faces declining interest in hard sciences (biology, chemistry, physics) and fragmented curricula, hindering the development of science-literate citizens amid challenges like energy poverty and food insecurity. Purpose: This study aimed to transform science education by designing an integrated, applied framework that fosters